¿Es esto periodismo, ciudadano? - Salvat Martinrey, Guiomar; Paniagua Santamaría, Pedro (Estudios sobre el Mensaje Periodístico, 2007)
The informative contributions that the citizens are making in the latest years by their own initiative through the electronic media are known as citizen journalism. The origin could be in the distrust of the audience faced with a traditional journalism excessively dependent on professional sources. It has been developed by the massive implantation of the information nets that make possible the digital technologies communications. It arises by initiative of the citizens, but when professionals and communications media are conscious of the great potential begins to become institutionalized. There are at least three realities that gather under this name but we can ask ourselves if they are in fact journalism.